Quilombolas et évangéliques : une incompatibilité identitaire ? Réflexions à partir d’une étude de cas en Amazonie brésilienne - Véronique Boyer (Journal de la Société des Américanistes)
« Quilombolas » and Evangelicans: incompatible identities? Reflexions on a case study in the Brazilian Amazon. Since 1988, many rural people base their legal demands over the land they occupy by claiming the status of communities reminiscent of quilombos. The paper first reviews the approach made by researchers of this field and the definitions they give to this contemporary phenomenon designated as « black rural communities ». A case study from the Middle Amazonas then allows the understanding of the basis of the disagreement and incomprehension between the crentes (literally believers, general term for Protestants) and the militants of the black movement. For the latter, the participation in this religious movement is generally understood as a factor of alienation that prevents the emergence of a black consciousness and hence the development towards political action.